(untitled) (The Conference Hub, 2025)
This article analyzes the essence, importance, and practical mechanisms of developing ethics and moral values among primary school students. The study scientifically explores the role of the school environment, pedagogical approaches, and cooperation with parents in fostering children’s personal qualities, social relationships, and spiritual worldview. It presents effective methods for instilling moral values through modern pedagogical strategies, interactive games, educational conversations, and exemplary behavior. Additionally, based on the analysis of foreign experiences, the article proposes suggestions and recommendations for the national education system.